Living with the Dead : Ancestor Worship and Mortuary Ritual in Ancient Egypt. - Harrington, Nicola (Havertown : Oxbow Books, 2012)
Living with the Dead presents a detailed analysis of ancestor worship in Egypt, using a diverse range of material, both archaeological and anthropological, to examine the relationship between the living and the dead. Iconography and terminology associated with the deceased reveal indistinct differences between the blessedness and malevolence and that the potent spirit of the dead required constant propitiation in the form of worship and offerings. A range of evidence is presented for mortuary cults that were in operation throughout Egyptian history and for the various places, such as the house.
Cover; List of figures and tables; Introduction; Acknowledgements; Timeline; Maps; CHAPTER 1: The Nature of the Deceased: Constituent Parts, Character, and Iconography; CHAPTER 2: The cult of the ancestors; CHAPTER 3: Places of interaction with the dead; CHAPTER 4: Times of interaction between the living and the dead:funerals, festivals, and banquets; CHAPTER 5: Attitudes to the dead; CHAPTER 6: Conclusions: living with the dead in ancient Egypt; Bibliography; Index.
Print version record.
Master record variable field(s) change: 072
Keywords: Funeral rites and ceremonies -- Egypt; Ancestor worship -- Egypt; SOCIAL SCIENCE -- Death & Dying; Ancestor worship; Funeral rites and ceremonies; Egypt; HISTORY / Ancient / Egypt; Electronic books